(untitled) (Bangladesh Journal of Bioethics, 2021)
The disability viewpoint is the fundamental for understanding social justice in a given population. Disability rights need to be obeyed in the inclusive preparedness and response to all the disasters or during the crisis period including COVID-19 pandemic. COVID-19 pandemic jeopardized the health and rehabilitation services globally. The impact is much more in low resource developing countries like Bangladesh. In general, people with disability (PWD) suffer from multiple medical and rehabilitation complications and they need frequent rehabilitation consultations or hospital admissions in comparison to people without disability. As a developing country, Bangladesh has poor ratios of doctors, nurses and technologists of 1:0.4:0.24 (WHO: 1:3:5) to face the COVID-19 challenge. Rehabilitation services have been disrupted in almost two-thirds (63%) of countries of the world. Even though rehabilitation is the key to recovery following severe illness from COVID-19. There are many concerns and debates about the preparedness, response and mitigation the process of COVID-19 on the part of the national government. According to recent study reports, the lives of about 100% of PWD have been impacted by the COVID-19 pandemic. COVID-19 National Technical Advisory Committee is working for strategic planning, response and mitigation process but omission of a representative of PWD or a rehabilitation physician in the committee has created much dissatisfaction. The difficult COVID-19 testing process due to country wide shutdown of rehabilitation essential services and central pulling of rehabilitation physicians have side lined the PWD inclusiveness. It is expected that the rehabilitation preparedness, response and mitigation of the pandemic should be based on an ethics driven process.